Obliquely incident ultrasonic wave propagation in a fluid–solid configuration and solid velocity measurements - Ji, Yunjia; Wang, Hua; Yang, Gengxiao; Bi, Qizhi (Ultrasonics, 2024)
•Emission angles of sources affect the accuracy of solid velocity measurement.•Deviation of incidence from critical angles reduces wave amplitude and frequency.•Adjusting offsets or incidence help P wave velocity extraction of slow solids.•Using S-wave first jump can avoid the interference of the leaky Rayleigh wave. Numerical analyses are performed to investigate ultrasonic wave propagation in fluid–solid half-spaces subject to a directional source. This research is particularly concerned with the behavior of refracted waves within fluid mediums and their utility in determining the acoustic velocities of solid materials. The simulations encompass solids with various mechanical parameters and highlight the influence of incident angles on wave propagation. The analysis reveals that as the disparity between incident and critical angles increases, both the dominant frequencies and amplitudes of the corresponding refracted waves decrease substantially, which is detrimental to the accurate extraction of solid velocities. For the low-velocity solid characterized by its shear wave velocity being less than the fluid’s acoustic velocity, refracted longitudinal waves are susceptible to interference from direct and reflected waves. This interference often results in underestimated velocity measurements. The challenge can be addressed by either extending the source-receiver offset or by adjusting the incident angle closer to the critical angle. Regarding solids with shear wave velocities exceeding the fluid’s acoustic velocity, although the velocity–time correlation (VTC) method can accurately determine longitudinal wave velocities, shear wave velocity extraction may be compromised by the presence of the leaky Rayleigh wave. We further compare velocities calculated by dividing the spacing distance of two receivers by the time difference of their respective wave packet arrivals. Results indicate that the initial trough and peak of the S wave packet are predominantly influenced by refracted shear waves and the leaky Rayleigh wave, respectively. This occurs because refracted shear waves propagate slightly faster than the leaky Rayleigh wave. Consequently, using the first trough of the shear wave packet as the wave onset can mitigate the impact of the leaky Rayleigh wave, yielding precise shear wave velocity measurements. These studies are of considerable importance for applications in geophysical downhole measurements and nondestructive testing.